International Trade in Services : Implications for the Fund - Tamirisa, Natalia (IMF Policy Discussion Papers; Policy Discussion Paper, 2003)
This paper reviews the characteristics of international trade in services and of the World Trade Organization's General Agreement on Trade in Services (GATS) framework, which was established to regulate it. Further liberalization of services trade in developing countries, as currently envisaged in the context of the WTO Doha Development Agenda, holds a number of potential benefits, such as underpinning the liberalization of goods trade, but it is also being resisted due to its potential adjustment costs. Two implications for IMF activities are examined: coherence among the three principal international economic institutions and sequencing with macroeconomic stabilization and regulatory reforms.